(untitled) (Journal of Academic Research, 2026)
There has been a recent increase in the incidence of urinary tract infections (UTIs) among individuals and a rise in bacterial resistance to antibiotics, leading to numerous complications. This study aimed to examine 86 urine samples from the Urology Department at Misurata Medical Center. The samples were cultured on different media, and diagnostic tests were conducted to identify the isolated bacterial species. The disk diffusion method was employed to test the susceptibility of these isolates to several antibiotics. The results revealed the isolation of several bacterial species in varying proportions: Staphylococcus aureus (36%), followed by Escherichia coli (23%), Klebsiella pneumoniae (11%), Klebsiella spp. (7%), Streptococcus spp. (5%), with Streptococcus viridans, Streptococcus pyogenes, and Proteus mirabilis each at 4%, and Pseudomonas aeruginosa, Enterobacter, and Bacillus sp. each at 2%. Furthermore, the findings indicated that among the Gram-negative bacteria, Pseudomonas aeruginosa exhibited the highest resistance to antibiotics (67%), followed by Klebsiella pneumoniae, Escherichia coli, and Proteus mirabilis (42%).